STRENGTH, COMPRESSIBILITY AND SWELLING CHARACTERISTICS OF CEPU CLAY - Arliansyah, Joni
STRENGTH, COMPRESSIBILITY AND SWELLING CHARACTERISTICS OF CEPU CLAY, JONI ARLIANSYAH, 1993, Program Magister Sistem dan Teknik Jalan Raya, Program Pasca Sarjana, Institut Teknologi Bandung. A study of the strength, compressibility and swelling characteristics of an expansive clay taken from the Cepu - Bojonegoro region of East Java has been undertaken. The study has involved standard classification testing, the determination of compressibility and drainage characteristics from consolidation testing using three different sample sizes in order to examine the effect of sample size, and the determination through testing of swelling potential and swelling pressure characteristics of reconstituted compacted samples, as well as undisturbed and air dried samples. Comparison was also made of the undisturbed strength as obtained in insitu measurement and in laboratory testing. The soils were found to be classified as inorganic clay of very high plasticity, having a very high swelling potential and very. poor characteristics for use as subgrade materials. The results of consolidation testing indicated that the compressibility and drainage characteristics in both vertical and horizontal directions would appear to be sensitive to sample size. The percentage swell of the Cepu clay was found to be very high, in all cases greater than 5 7., and influenced by compaction effort and surcharge weight. The swelling potential found from samples with modified compaction was higher than that for samples tested after preparation at standard compaction. Surcharge reduced the extent of swelling. The swelling pressure for reconstituted samples indicated that swelling pressure increased as the initial water content decreased. For air dried sample preparations, water content decreased causing an increase in dry density and swelling pressure and the results indicated that drying the sample in air could be effective in indicating the swelling behaviour of soil which has dried in the field. The insitu undrained shear strength was found to vary at three sections where the test was undertaken, and the values obtained increased from a negligible value at the surface to reach an approximately constant value at 1.0 to 2.0 metres depth. For cohesive soil, such as Cepu, the vane shear test was found to be effective in determining the insitu strength characteristics of the soil